2020
DOI: 10.1007/s00415-020-09769-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anti-epileptic drug choice on discharge in acute traumatic brain injury patients

Abstract: Background Anti-epileptic drug (AED) prophylaxis in the first-seven days post-traumatic brain injury (TBI) is known to reduce seizure frequency acutely. AED efficacy is equivalent; therefore, choice of AED may rest with their side-effects. We hypothesise that AEDs that impair balance will prolong recovery, shown by a longer hospital stay. We compared length of hospital stay (and reported dizziness) in TBI patients receiving the commonest AEDs used in our TBI patients, Phenytoin (which may cause imbalance), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
1
9
0
6
Order By: Relevance
“…Recent studies have demonstrated no evidence that early treatment with ASMs reduces the risk of LPTS or mortality, whereas it seems to adversely affect functional outcome in the long term 14 , 19 , 33 , 41 , 44 46 . Levetiracetam, used for early post-TBI seizure prophylaxis, seems to be associated with a shorter length of hospital stay than phenytoin 21 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies have demonstrated no evidence that early treatment with ASMs reduces the risk of LPTS or mortality, whereas it seems to adversely affect functional outcome in the long term 14 , 19 , 33 , 41 , 44 46 . Levetiracetam, used for early post-TBI seizure prophylaxis, seems to be associated with a shorter length of hospital stay than phenytoin 21 .…”
Section: Discussionmentioning
confidence: 98%
“…In fact, the recent Brain Trauma Foundation Guidelines 20 recommended the use of prophylactic therapy to decrease the incidence of EPTS within 7 days after severe TBI. Historically, phenytoin has been the ASM of choice as prophylactic therapy, but its complications have led to increasing use of levetiracetam as a substitute 21 . Even on this aspect, there is no clear evidence in the literature 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Seluruh pasien mendapatkan AED berdasarkan kecurigaan klinis berupa kejang maupun memiliki lokasi patologi intrakranial pada CT scan. Adapun dosis rutin yang diberikan adalah fenitoin 300 mg sekali sehari dan levetiracetam 500 mg dua kali sehari kecuali terdapat perbedaan berat badan maupun usia (Harris et al, 2020).…”
Section: Karakteristik Partisipanunclassified
“…Pusing lebih sering terjadi pada pasien yang diobati dengan fenitoin dengan presentase 26% dibandingkan pusing yang terjadi pada pasien yang diobati dengan levetiracetam dengan presentase 8%. Diketahui bahwa tidak ditemukan adanya korelasi antara skor total GCSdan durasi lama tinggal pasien di trauma unit (Harris et al, 2020).…”
Section: Hasil Dari Literatur Yang Digunakanunclassified
“…Зазначимо, що на сьогодні не застосовують профілактичне лікування епілепсії при будьякій черепномозковій травмі, як це було прийнято ба гато років у нейрохірургів, навіть за відсутності нападів у гострий період травми. Але це не стосується тяжкої черепномозкової травми, оскільки в даний час рекомендується для запобігання раннім нападам застосовувати леветирацетам (кращі результати) або фенітоїн протягом щонайменше 1-2 тиж, якщо користь пере важає ризики [13]. Іноді лікування продовжують до 6 міс.…”
Section: структурна судинна епілепсія (постінсультна при хворобі дрібних церебральних судин)unclassified